Children’s Toy Safety Standards in Malaysia and ASEAN: Towards Single Regional Regulation of Lead-Based Paints and Children Toys - Haniff, Wan Amir Azlan Wan; Ismail, Rahmah; Isa, Suzanna Mohamed; Fadzil, Rozlinda Mohamed; AlSagoff, Syed Sagoff; Khalid, Kartini Aboo Talib @; Hassan, Hakimi; Mohamed, Nurina Awanis (International Journal of Asian Social Science, 2020)
Children’s toys have always been the primary step on the manufacturing ladder for several developing economies like Malaysia and other ASEAN member states (AMS). Apart from an ideal product to chase low cost labor, children’s toys were easy to produce with relative low-quality requirements. However, following the ‘Year of the Recall’ in 2007 which saw the greatest number of recalled products of children’s toys from markets due to higher permissible amount of lead, Malaysia and several AMS no longer taken the safety of children’s toys product lightly. Despite Malaysia has amended its regulations which requires toys available on the Malaysian markets to be tested for the presence of maximum acceptable levels of lead from toy materials and toy parts, Malaysia and several AMS still has no laws on the regulation on the amount of lead in paint. Even worse, some of AMS still has no national legislations and regulations for safety standard of children’s toys product. This qualitative research utilizes the secondary data gained from scientific database analysis and library research including documents and precedents on children toy safety regulations and analyzed this data by legal interpretation. The finding shows that AMS requires proper national and regional legislations and regulations particularly for import, export, manufacturing, adoption and sale of children toys and paints to be ratified and implemented so as to avert the availability of lead-based paints and children toys with high lead content in the market.